Hubungan Pengetahuan dan Sikap tentang Penyakit Skizofrenia terhadap Stigma Masyarakat pada Penderita Skizofrenia di Desa Kersamanah Kecamatan Kersamanah Kabupaten Garut - Susan Susyanti; Vina Hapsari (Jurnal Medika Cendikia, 2018)
The phenomenon of interference of the soul is currently undergoing significant improvement and each year the number of sufferers of the disorder of the soul. Based on data from the World Health Organization (WHO), there are about 450 million people in the world who experience the disorder. This is because the public does not realize that the symptoms experienced by that time an early symptom of the disorder. Knowledge society can affect towards attitudes and stigma in people with schizophrenia. The general objective of this research is to know the relation of knowledge and attitudes about the stigma against schizophrenia disease society at Kersamanah village schizophrenia sufferers Subdistrict Kersamanah Garut 2016. The research is the study of the non descriptive analytic method with experiments with cross sectional approach, the population in this study there are 1324 respondents, and a sample of 90 respondents. The analysis used is using chi square. The results of the univariate that public knowledge about the disease schizophrenia most (52.2%) of the respondents less knowledgeable, and very little (16.7%) of respondents knowledgeable good. the attitude of the respondent filmed (72%) of respondents did not support the attitude and the stigma of a part (62.2%) of respondents have a negative stigma is huge. The results of the research there were relationship proves that bivariat description, the knowledge about the disease of schizophrenia with the stigma of the society on a schizophrenic (P-value = 0,020), stigma society on schizophrenics (P-value = 0.003). The conclusion that there is a meaningful relationship between knowledge and attitudes about the disease of schizophrenia with the stigma of the society on the schizophrenic. It is hoped this research can be used as input for the profession related to provide health education so that it can increase of the people knowledge.